Structural characterization of V57D and V57P mutants of human cystatin C, an amyloidogenic protein. (24th March 2013) - Orlikowska, Marta; Szymańska, Aneta; Borek, Dominika; Otwinowski, Zbyszek; Skowron, Piotr; Jankowska, Elżbieta
<x xml:space="preserve">Abstract</x> Wild‐type human cystatin C (hCC wt) is a low‐molecular‐mass protein (120 amino‐acid residues, 13 343 Da) that is found in all nucleated cells. Physiologically, it functions as a potent regulator of cysteine protease activity. While the biologically active hCC wt is a monomeric protein, all crystallization efforts to date have resulted in a three‐dimensional domain‐swapped dimeric structure. In the recently published structure of a mutated hCC, the monomeric fold was preserved by a stabilization of the conformationally constrained loop L1 caused by a single amino‐acid substitution: Val57Asn. Additional hCC mutants were obtained in order to elucidate the relationship between the stability of the L1 loop and the propensity of human cystatin C to dimerize. In one mutant Val57 was substituted by an aspartic acid residue, which is favoured in β‐turns, and in the second mutant proline, a residue known for broadening turns, was substituted for the same Val57. Here, 2.26 and 3.0 Å resolution crystal structures of the V57D andV57P mutants of hCC are reported and their dimeric architecture is discussed in terms of the stabilization and destabilization effects of the introduced mutations.